THE EFFECT OF SENIOR MANAGEMENT CHANGE ON ORGANISATIONAL CULTURE - EGBUSON, ALERO (2009)
The aim of this dissertation is to investigate the effect of senior management change on organisational culture. In this case we have chosen Guinness Nigeria PLC to investigate culture change as a result of transition in management from Expatriate to Indigenous managers. Data collection methods such as semi-structured interviews, observation of the physical surroundings and historical document review were employed in this study. Multiply methods were employed to applied for a more robust and rich data. The resultant research is then interpreted through a mesh through my experiences and a reflexive approach was employed identify the researchers bias that may occur whilst interpreting the data. A case study approach was then employed to encompass the variety of data collected which was codified into thematic narratives. This answered the question “How has this transition in senior management affected the organisational culture?”, “Are senior management the biggest influences on culture?” and “How was culture change envisaged by members of the organisation”. This dissertation gives an insight into the role local values play in organisational culture, how these values may be ignored by Expatriate managers and later surfaced when local managers take over senior management positions. This then has a great impact on the values and norms in the organisation. These changes however had a varying effect on individuals; however the merger with Grand metropolitan to form Diageo also had an effect on organisational culture. This dissertation concludes with the notion that the merger may have had a greater effect on organisational culture than the transition in senior management. It also posits that western bureaucratic style of management may be effective when expatriates hold the managerial positions, but may not be so when the baton is passed on to indigenous managers who are guided more by local values.